Interfaces entre juventude e vocação. Uma análise qualitativa no Rio de Janeiro - Fernandes, Sílvia Regina Alves (Revista Eclesiástica Brasileira, 2019)
Este artigo analisa as motivações de jovens – rapazes e moças – no Rio de Janeiro para o ingresso em seminários e conventos, respectivamente. O paper resgata alguns resultados da pesquisa de doutorado que analisou os discursos de 35 rapazes e moças que se percebem como “vocacionados”. Representações da juventude e do “chamado vocacional” são alguns dos temas abordados e que revelam aspectos relevantes para a construção da vocação religiosa em tempos de modernidade avançada e transformações das identidades. Abstract: This article analyzes the motivations of young – youngsters and young women – in Rio de Janeiro for the ingression in seminaries and convents, respectively. Paper rescues some results of the PhD research of that it analyzed the speeches of 35 youngsters and young women whom themselves perceive as “called”. Representations of youth and the “vocational call” are some of the boarded subjects and that they disclose to important aspects for the construction of the religious vocation in times of advanced modernity and transformations of the identities.